1983
DOI: 10.1029/wr019i006p01547
|View full text |Cite
|
Sign up to set email alerts
|

Water movement into seasonally frozen soils

Abstract: Many floods of record in cold regions are produced b_y s_n9w ablation. Accurate prediction of snowmelt runoff events by using computer models hinges upon an accurate understanding of the hydrologic role of frozen soils. This paper discusses the redistribution of soil moisture that takes place during the development of seasonal frost in a silty loam soil and the infiltration characteristics of this seasonally frozen soil. Depending upon the total (water and ice) soil moisture conditions near the ground surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
154
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(162 citation statements)
references
References 8 publications
8
154
0
Order By: Relevance
“…Infiltration of meltwater from the snow cover may cause significant warming in frozen soils, which is revealed by a sudden temperature shift to the melting point in near-surface layers (Kane and Stein, 1983;Boike et al, 1998;Ishikawa et al, 2006). Similar temperature shifts were reported for the high-elevation permafrost station at Schilthorn, Swiss Alps (2970 m a.s.l.)…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Infiltration of meltwater from the snow cover may cause significant warming in frozen soils, which is revealed by a sudden temperature shift to the melting point in near-surface layers (Kane and Stein, 1983;Boike et al, 1998;Ishikawa et al, 2006). Similar temperature shifts were reported for the high-elevation permafrost station at Schilthorn, Swiss Alps (2970 m a.s.l.)…”
Section: Introductionsupporting
confidence: 61%
“…Kane and Stein, 1983;Outcalt et al, 1990;Romanovsky and Osterkamp, 2000). Unfrozen moisture can exist at sub-zero temperatures and advective water migration to the freezing front can redistribute water and ice, thus changing the thermal and hydrological properties of the soil (Kane and Stein, 1983;Trimble et al, 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field experiments to determine infiltration rates into frozen soil are not easy to conduct since there are many technical difficulties to overcome. Kane and Stein [1983], Granger et al [1984], Karvonen et al [1986], and others used methods that are commonly applied to unfrozen soils. These field experiments gave valuable understanding of the dominating factors in the snowmelt runoff/infiltration process.…”
Section: Introductionmentioning
confidence: 99%
“…Many field studies of snowmelt infiltration into frozen soils are reported in the literature (e.g., Willis et al 1961;Kane 1980;Kane and Stein 1983;Granger et al 1984;Gray et al 1985;Burn 1990;Woo and Marsh 1990). These studies show that the cumulative infiltration of meltwater released by a seasonal snowcover (seasonal infiltration) varies directly with the snow water equivalent and inversely with the total water (liquid + ice) content of the soil at the time of melt.…”
mentioning
confidence: 99%